Prevalence of Diastasis Recti Abdominis in Females with Respect to Their Stage and Status of Pregnancy - Sana Hafeez, Tasmia Irum Noureen Shakir Baig, Muhammad Ali, Hania Hafeez, Ashley Nudrat, Hira Butt (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the prevalence of diastasis recti abdominis in females with respect to their stage and status of pregnancy Methodology: A cross sectional study was conducted in Lahore General Hospital from September 2018 to January 2019.Child bearing female in the age group of 20-40 years. Child bearing females not willing to participate, menopausal females, females with any gynecological disorders and those who suffered from ectopic pregnancy were excluded from the study. The questionnaire distributed as hand-outs in selected hospitals. Data was collected in person/ through representatives appointed in every hospital. Results: There was no statistically significant association between previous pregnancy and presence of Diathesis Recti (P=0.566). A statistically significant association between status of pregnancy and presence of Diathesis Recti was present (p≤0.001). Conclusion The prevalence of Diathesis Recti was higher in the females who did not have a history of previous pregnancy.The presence of Diathesis Recti was the highest in females in their third trimester while those in the first and second trimester did not suffer from this condition. It was also seen that the non-pregnant females suffered more from the condition in comparison to the pregnant women. Keywords: Diathesis Recti, Pregnant females, Non-pregnant females, trimester.